Depletion of Demethylase KDM6 Enhances Early Neuroectoderm Commitment of Human PSCs - Meng, Yajing; Zhang, Tianzhe; Zheng, Ran; Ding, Song; Yang, Jie; Liu, Ran; Jiang, Yingan; Jiang, Wei (Frontiers in Cell and Developmental Biology, 2021)
Epigenetic modifications play a crucial role in neurogenesis, learning and memory, but the study of their role in early neuroectoderm commitment from pluripotent inner cell mass is relatively lack. Here we utilized the system of directed neuroectoderm differentiation from human embryonic stem cells and identified KDM6B, an enzyme responsible to erase H3K27me3, was the most upregulated enzyme of histone methylation during neuroectoderm differentiation by transcriptome analysis. We then constructed KDM6B-null embryonic stem cells and found strikingly, the pluripotent stem cells with KDM6B knockout exhibited much higher neuroectoderm induction efficiency. Furthermore, we constructed a serial of embryonic stem cell lines knocking out the other H3K27 demethylase KDM6A, and depleting both KDM6A and KDM6B, respectively. These cell lines together confirmed KDM6 impeded early neuroectoderm commitment. By RNA-seq, we found the expression levels of a panel of WNT genes were significantly affected upon depletion of KDM6. Importantly, the result that WNT agonist and antagonist could abolish the differential neuroectoderm induction due to manipulating KDM6 further demonstrated WNT was the major downstream of KDM6 during early neural induction. Moreover, we found the chemical GSK-J1, an inhibitor of KDM6, could enhance neuroectoderm induction from both embryonic stem cells and induced pluripotent stem cells. Taken together, our findings not only illustrated the important role of histone methylation modifier KDM6 in early neurogenesis, providing insights into the precise epigenetic regulation in cell fate determination, but also showed the inhibitor of KDM6 could facilitate neuroectoderm differentiation from human pluripotent stem cells.